2013
DOI: 10.1037/a0031002
|View full text |Cite
|
Sign up to set email alerts
|

Over a half-century encapsulated: A multicultural content analysis of the Journal of Counseling Psychology, 1954–2009.

Abstract: Articles including multicultural content published in the Journal of Counseling Psychology (JCP), from 1954 to 2009, were examined for themes. Multicultural content in this study was broadly defined to include the following identities: race/ethnicity, gender/sex, religion/spirituality, sexual orientation, social status, disability, age, and intersections. Inclusion of articles focused on each of these identity domains was reported by decade. Gender/sex was the most prevalent multicultural identity found in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 29 publications
2
47
1
1
Order By: Relevance
“…The third compares the content of two journals over an extended period of time, such as the contents of CDQ and JVB (Buboltz, Ebberwein, Watkins, & Savickas, ). The fourth analyzes journal content related to a specific topic for one journal, such as multicultural concepts (Arredondo, Rosen, Rice, Perez, & Tovar‐Gamero, ; Lee et al, ), or a specific topic in multiple journals, such as the career development of gay men (Buhrke, Ben‐Ezra, Hurley, & Ruprecht, ) or American Indian secondary school students (Flynn, Duncan, & Evenson, ).…”
Section: Content Analyses Of Journal Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The third compares the content of two journals over an extended period of time, such as the contents of CDQ and JVB (Buboltz, Ebberwein, Watkins, & Savickas, ). The fourth analyzes journal content related to a specific topic for one journal, such as multicultural concepts (Arredondo, Rosen, Rice, Perez, & Tovar‐Gamero, ; Lee et al, ), or a specific topic in multiple journals, such as the career development of gay men (Buhrke, Ben‐Ezra, Hurley, & Ruprecht, ) or American Indian secondary school students (Flynn, Duncan, & Evenson, ).…”
Section: Content Analyses Of Journal Articlesmentioning
confidence: 99%
“…Content analyses of journal articles provide an opportunity for a discipline to periodically evaluate the congruence of the professional literature with the discipline's purpose, interests, and values (Buboltz, Deemer, & Hoffman, 2010;Lee, Rosen, & Burns, 2013). Journal article content analyses also identify trends and changes, which likely affect counseling practice (Loveland, Buboltz, Schwartz, & Gibson, 2006;Williams & Buboltz, 1999).…”
Section: Content Analyses Of Journal Articlesmentioning
confidence: 99%
“…The multicultural identity categories used in our study were selected based on published reviews of multicultural research in other journals (D.L. Lee et al, ) and therefore included gender, social class, sexual orientation, gender identity, ability status, religion/spirituality, age, immigration, and international status. We did not include race/ethnicity because this content was captured by a more recent review (i.e., B.H.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…Comprehensive reviews of multicultural content in related journals, such as the Journal of Counseling Psychology ( JCP ), have revealed greater attention to some multicultural identity domains and neglect of others. Specifically, a review of multicultural content in JCP showed increasing attention to gender but minimal attention to sexual orientation, disability, religion, and social class from 1954 to 2009 (D. L. Lee, Rosen, & Burns, ). Identification of multicultural identity groups that have received insufficient attention in the literature is important, as this neglect could lead to ineffective career counseling practices.…”
mentioning
confidence: 99%
“…Embora tais pressupostos teóricos possam parecer, em um primeiro momento, distantes, têm se mostrado relevantes na estruturação da oferta de apoio psicológico às pessoas que participam da comunidade religiosa retratada neste estudo de caso. O aconselhamento multicultural (Lee, Rosen, & Burns, 2013;Sehgal, Saules, Young, Grey, Gillem, & Nabors, 2011), fortemente desenvolvido nos Estados Unidos para o atendimento de diferentes etnias, culturas e imigrantes, por exemplo, destaca a necessidade de o conselheiro (ou terapeuta) incorporar elementos da cultura de referência do cliente para poder ouvi-lo com mais propriedade, trazendo à baila os elementos culturais que constituem o cliente e sua comunidade. Assim, toda orientação deve partir desse universo de crenças, saberes e práticas no qual o cliente está imerso, não podendo o aconselhamento partir de elementos externos a essa comunidade cultural, evitando o olhar etnocêntrico por vezes atribuído a quem se coloca "de fora" da comunidade de referência.…”
Section: Introductionunclassified